Generational differences in job engagement: a case study of an industrial organization in Iran. Issue 3 (6th March 2017) - Akhavan Sarraf, Ahmad Reza; Abzari, Mehdi; Nasr Isfahani, Ali; Fathi, Saeed
Abstract : Purpose: Understanding generational differences are important because generational diversity can affect work relationships and the effectiveness of communication, engagement and performance management strategies. On the other hand, organizations should be concerned about employee engagement, considering all the positive outcomes that engaged employees could bring to the workplace. The paper aims to discuss these issues. Design/methodology/approach: The purpose of this study is to examine employee engagement of different generations in Iran. Four hypotheses were proposed regarding job engagement and its constructs: vigor, dedication and absorption. The study utilized ANOVA tests to detect statistically significant differences between generations. Findings: The results revealed not only a number of significant differences among generations, but also some similarities. The study shows the value of generational analysis as a useful segmentation criterion in organizational behavior researches. Originality/value: To distinguish between different generations in relation to job engagement, also better understanding the behavior of generational cohorts that affect the success of organizations. It helps managers to find and resolve the conflict among persons and groups in the organization and also to achieve the benefits of diversity, creativity and energy of generations.